Lower Ureteral Obstruction and Leakage in the First Month Following Renal Transplantation - Abdul muhsin, Ausama i Saad; Alnasiri, Usama S; Rifat, Usama N (AL-Kindy College Medical Journal, 2007)
Background: Transplantation has revolutionized treatment of end- stage renal disease (ESRD) by proving more cost effective than hemodialysis, with a lower morbidity and improved quality of life. Objective: To evaluate the development of these complications in the first month postoperatively and correlate their development to the type of donation whether related or unrelated. Methods: Fifty (50) patients aged (15-62) years, with a mean age (34.46 ± 12.4 SD) years with (ESRD), who underwent renal transplantation from September 2000 to October 2002, were followed-up for one month postoperatively clinically and by assessment of renal function tests, sonographic and Doppler examinations. Ureteral obstruction was considered in those patients who had allograft dysfunction, ultrasonic evidence of peritransplant collection, moderate-severe dilatation of upper urinary tract of transplanted kidney and postoperative ipsilateral or bilateral leg edema. Ureteral leakage was considered in those patients who had persistent drainage of urine with or without allograft dysfunction. Two patients were excluded from the followup due to death in the first 24-hour postoperatively. Results: Six (6) patients (12.5% of cases) developed ureteral obstruction due to peri-ureteral fluid collection. In five patients the collection decreased and upper urinary tract dilatation improved gradually, as shown by ultrasound, on watchful waiting. One patient had surgical evacuation of a large hematoma. Four (4) patients (8.3% of cases) developed ureteral leakage. The leakage stopped in one patient after keeping the urethral catheter for a longer period. Three patients had surgical exploration due to persistent urinary leakage. Redo implantation of allograft ureter was done in two cases. Development of ureteral complications was compared with the type of donation (related or unrelated). The comparison was not statistically significant. Conclusions: The development of ureteral complications in not related to the type of donation. Extravesical ureteral anastamosis with the use of a stent is less likely to be associated with postoperative ureteral complications.